Effect of heat treatment on microstructure and mechanical properties of boron containing Ti-Stabilized AISI-321 steel for nuclear power plant application. (March 2021) - Kasana, Shivraj Singh; Pandey, O.P.
Highlights: 30 ppm boron addition to AISI 321 steel improved the mechanical properties both at room and elevated temperature. Boron addition to the AISI 321 steel decreased sensitization and reduced intergranular corrosion. Boron addition makes the AISI 321 steels suitable material for VVER type nuclear reactors. Abstract: Effect of boron on microstructure and its influence on elevated temperature properties of titanium stabilized AISI 321 steel was studied. A comparative study on mechanical properties of AISI 321 steels with and without boron addition is done. Both steels were worked to get appropriate reduction using forging-rolling process followed by solution annealing (SA) and stabilizing treatment (ST) at the appropriate temperature. Optical micrographs revealed uniform distribution of precipitates in steel. The precipitate count for Ti-stabilized AISI 321 steel with 30 ppm boron (TB30) was higher than Ti-stabilized AISI 321 steel (TB1) in which TiN and TiCN precipitates were observed. In addition to this, for TB30 steel containing boron precipitates of Fe2 B and Cr2 B were also observed. Precipitates refined the austenite matrix and provided yield strength stability to the AISI 321 steels. Boron addition in TB30 steel improved YS and UTS of AISI 321 steel with a marginal loss in ductility. SA and ST, TB30 steel exhibited best mechanical properties at room and elevated temperature (350 °C). Further, quantification of intergranular corrosion was done by sensitization of samples at 675⁰C for one hour and evaluated as per ASTM A262 specification practice A and practice E. Addition of nearly 30 PPM boron is highly beneficial in titanium stabilized AISI 321 steel that led to increased resistance to sensitization (both according to practice A and practice E) and improved the microstructural stability at elevated temperature resulting a reduction in intergranular corrosion and improved the elevated temperature mechanical properties. Thus, SA and ST, TB30 steels showed superior results as compared to TB1 steel. Study shows that TB30 steel is more suitable material to replace the cooling water inlet and outlet tubes of VVER type nuclear reactor.